Karakteristik Nikel Laterit di Blok Lara, Kabupaten Morowali Utara, Provinsi Sulawesi Tengah - Natua, Moh Rizky A R; Permana, Aang Panji; Zainuri, Ahmad (Jurnal Pendidikan Geografi Undiksha, 2024)
The research was conducted in Towara Village, East Petasia District, North Morowali Regency, Central Sulawesi Province. with a research area of ±17 ha. The methods used in this research are geological survey, drill logging and petrographic analysis. The geomorphological unit at this research location is Anthropogenic with a gentle - steep slope  and a steep - very steep slope. The lithology at this location is serpentinized peridotite and serpentinized Harsburgite units. The cross-section of laterite nickel deposits consists of several zones, namely topsoil, limonite, saprolite and bedrock. Top soil is composed of loose sand-clay sized material which is generally blackish in color with high organic content and iron oxide in the form of soil. The thickness of the soil cover ranges from 1 meter to. 2 meters and generally does not contain significant nickel. The limonite zone is generally blackish brown in color and contains hematite and goethite along with a number of elements such as aluminum, manganese and chromium. Thickness 3 meters to 7 meters. The saprolite zone generally in the research area has an average thickness of 3 – 6 meters, with color variations starting to appear, namely light brown, light green, gray and yellow. Bedrock is the lowest part of the Nickel Laterite profile, consisting of blocks of bedrock with a size of > 60 cm.